2001
DOI: 10.1212/wnl.56.7.849
|View full text |Cite
|
Sign up to set email alerts
|

Familial cerebellar ataxia with muscle coenzyme Q10 deficiency

Abstract: Primary CoQ10 deficiency is a potentially important cause of familial ataxia and should be considered in the differential diagnosis of this condition because CoQ10 administration seems to improve the clinical picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
162
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(168 citation statements)
references
References 19 publications
4
162
1
Order By: Relevance
“…Five clinical subtypes have been recognized: (1) Encephalomyophatic, with mitochondrial myopathy, recurrent myoglobinuria and CNS symptoms and signs; (2) Early infantile multisystemic, with severe visceral and brain manifestations; (3) Leigh syndrome; (4) Pure myopathic; (5) Ataxic 14,15,17 .…”
Section: Ataxia With Coenzyme Q10 Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Five clinical subtypes have been recognized: (1) Encephalomyophatic, with mitochondrial myopathy, recurrent myoglobinuria and CNS symptoms and signs; (2) Early infantile multisystemic, with severe visceral and brain manifestations; (3) Leigh syndrome; (4) Pure myopathic; (5) Ataxic 14,15,17 .…”
Section: Ataxia With Coenzyme Q10 Deficiencymentioning
confidence: 99%
“…Early symptoms might include developmental delay, hypotonia and frequent falls. Global, progressive ataxia, and dysarthria start before the adolescence 17 . Epileptic seizures, proximal or distal muscle weakness, dysphagia, ophthalmoparesis, nystagmus, peripheral axonal neuropathy, pyramidal signs and scoliosis might also be present 14,15,17 .…”
Section: Ataxia With Coenzyme Q10 Deficiencymentioning
confidence: 99%
“…His siblings showed similar improvements. In addition, seizures in the affected sister disappeared on CoQ 10 therapy and her anti-convulsant medication was discontinued (Musumeci et al, 2001). In these 3 patients, we demonstrated that CoQ 10 deficiency was secondary to a stop codon mutation in the APTX gene, which is known to cause ataxia-oculomotor-aprataxia 1 (AOA1) (Quinzii et al, 2005,Date et al, 2001Moreira et al, 2001).…”
mentioning
confidence: 90%
“…Primary CoQ 10 deficiency causes clinically heterogeneous diseases: 1) encephalomyopathy characterized by the triad of recurrent myoglobinuria, brain involvement and ragged-red fibers (Ogasahara et al, 1989;Sobreira et al, 1997;Boitier et al, 1998;DiGiovanni et al, 2001;Aure et al, 2004); 2) severe infantile multisystemic disease (Rötig et al, 2000;Rahman et al, 2001;Salviati et al, 2005); 3) cerebellar ataxia (Musumeci et al, 2001;Lamperti et al, 2003;Gironi et al, 2004;Artuch et al, 2006); 4) Leigh syndrome with growth retardation, ataxia and deafness (Van Mardergem et al, 2002); and 5) isolated myopathy (Lalani et al, 2005;Horvath et al, 2006). These disorders are transmitted as autosomal recessive traits and in most cases respond to CoQ 10 supplementation.…”
mentioning
confidence: 99%
See 1 more Smart Citation